PERAN GURU SEBAGAI INSPIRATOR DALAM MENANAMKAN NILAI KARAKTER DISIPLIN PADA MATA PELAJARAN PKN (STUDI KASUS KELAS II SDN 011 LENGGADAI HULU KABUPATEN ROKAN HILIR) - Eka Setianingsih; Zaka Hadikusuma Ramadan (STKIP Subang, 2026)
This study aims to describe and analyze the teacher's role as an inspirer in instilling the character value of discipline during Civics Education (PKn) lessons for second-grade students at SD Negeri 011 Lenggadai Hulu, Rokan Hilir Regency. A qualitative descriptive approach using a case study design was employed; the research subjects included three second-grade teachers (homeroom teachers for classes IIA, IIB, and IIC) and five students. Data collection involved direct observation, in-depth (semi-structured) interviews, and document analysis. Data validity was verified through source and technique triangulation, while data analysis proceeded through stages of reduction, presentation, and conclusion drawing. The results indicate that the second-grade teachers successfully fulfilled their roles as humanistic inspirers through five key indicators: setting a tangible example (modeling) regarding punctuality and neat attire; democratically formulating class rules as facilitators; implementing positive discipline without verbal abuse as motivators; optimizing non-media reinforcement (body language and verbal praise) as mediators amidst limited visual teaching aids; and conducting periodic guidance and evaluation that led to a rise in students' conscious compliance. The primary obstacle a discrepancy in disciplinary patterns between the school and home environments was effectively addressed by the teachers through continuous role modeling, the reinforcement of religious moral values within Civics lessons, prayer, and harmonious communication and coordination with parents.